Pengaruh Pengambilan Keputusan dan Komunikasi terhadap Kinerja Aparatur Sipil Negara (ASN ) pada Dinas Komunikasi dan Informatika Kota Makassar - Amiruddin, Amiruddin (CV. Ulil Albab Corp, 2023)
The purpose of this study is to explain the effect of decision making and communication on employee performance. To find out how big the influence of decision making on employee performance, to find out how much influence communication has on employee performance at the Makassar City Communication and Information Office. The type of research used is quantitative, with a population of 45 at the same time being a sample or respondent which is called a saturated sample. The data were collected using a questionnaire that had been tested for validity and reliability, and the analytical technique used was the classical assumption test, the data analysis method used multiple linear regression with t test (partial), f test (simultaneous), and determination test (R2) using the program SPSS Version 23. The results of this study indicate that partially the decision-making and communication variables have a positive and significant effect on employee performance. And the variables of decision making and communication have a simultaneous effect on employee performance at the Makassar City Communication and Information Office.